A new and correct map of North America, with the West India Islands, divided according to the last Treaty of Peace, Concluded at Paris, the 20th of Jan. 1783, wherein are particularly Distinguished, the thirteen Provinces wich Compose The United States of North America- [arkusz 1] - Lotter, Tobias Conrad (1717-1777) (Lotter, Tobias Conrad (1717-1777), 1748)
miedzioryt ręcznie kolorowany podziałka liniowa: Geometrical Miles 60 to a Degree: 255 – 8,5 cm arkusz tytułowy mapy z ozdobnym kartuszem, 1 mapa w 4 arkuszach, legenda, mapy poboczne: A Particular Map of Baffin and Hudson's Bay The Passage by Land to California Discover'd by Father Eusebius Francis Kino opis fiz.: około 50x57cm